Rekonstruksi Pemikiran Ekonomi Islam tentang Pasar dalam Ekonomi Modern - Syahrul Abadi; Muhammad Yafiz (Journal of Islamic Economic Studies, 2025)
Islamic economic thought on the market has strong historical roots and distinctive normative values, yet it faces significant challenges within the dynamics of the modern economy characterized by globalization, digitalization, and the dominance of free-market mechanisms. This study is motivated by the gap between Islamic market principles and modern market practices that often generate inequality and injustice. The purpose of this study is to reconstruct Islamic economic thought on the market to ensure its relevance in modern economic development without losing its core values. This research employs a literature analysis method by examining classical and contemporary Islamic economic works alongside relevant modern economic literature. The results indicate that Islamic market concepts emphasize justice, transparency, prohibition of exploitation, and the moral role of market actors, which can be reconstructed through the integration of Islamic ethical values into modern market systems. The implications of this study demonstrate that reconstructing Islamic market thought can contribute theoretically to contemporary Islamic economics and practically offer an alternative framework for developing a just and sustainable market system.